2021
DOI: 10.1186/s12873-021-00491-7
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic: the effect on airway Management in non-COVID emergency patients

Abstract: Background During the COVID-19 outbreak, healthcare providers might have avoided droplet/aerosol-generating procedures, such as non-invasive ventilation (NIV) and high-flow nasal cannula (HFNC) due to the concern of themselves being infected. We hypothesized that this change of practice could have also occurred to other non-COVID-infected patients in the Emergency Department (ED). Methods A retrospective analytic study was conducted in the ED of Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…After the first confirmed case of COVID-19 in Taiwan in January 2020, both personal protective equipment and critical care resources have been impacted by the pandemic. The outbreak has severely impacted the daily practice of public health and palliative care globally, and consequently a balance should be struck between intensive care unit (ICU) utilization and hospice medication [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the first confirmed case of COVID-19 in Taiwan in January 2020, both personal protective equipment and critical care resources have been impacted by the pandemic. The outbreak has severely impacted the daily practice of public health and palliative care globally, and consequently a balance should be struck between intensive care unit (ICU) utilization and hospice medication [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This qualification suggested that these noninvasive respiratory support modalities might increase the risk of SARS-CoV-2 transmission to health care workers and therefore advised limiting their use, preferentially placing patients receiving HFNO or NIV in airborne infection isolation rooms and wearing a respirator rather than a medical mask when entering the room of patients with suspected or confirmed infection . The guidelines provided little or no data supporting the designation of HFNO and NIV as AGPs, however, which may have led to misdirected resources and confusion …”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10] The guidelines provided little or no data supporting the designation of HFNO and NIV as AGPs, however, which may have led to misdirected resources and confusion. 7,[11][12][13][14][15] Ideally, risk stratification for respiratory support modalities should be based on randomized clinical trials assessing associations between their use and health care worker infections. However, such studies have not been performed, and it is unlikely that they will be, given the complexity of randomizing critically ill patients and strained health care staff as well as the difficulty of attributing health care worker infections to specific exposures given the high prevalence of SARS-CoV-2 in the general community.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Many acute care hospitals mandated changes in routine processes of patient care to avoid and reduce in-hospital transmission of COVID-19, including universal masking, 13 , 14 visitor restriction policies, 15 , 16 and extra precautions for aerosol generating medical procedures (AGMP). 17 19 Training programs also had to adjust to the increasing numbers of patients while mitigating risk. 20 , 21 At the academic hospitals affiliated with the University of Toronto where the authors practice, this involved redeploying residents to the IM clinical teaching units, establishment of COVID-19 teams, and a restructuring of resident call to separate daytime and nighttime shifts.…”
Section: Introductionmentioning
confidence: 99%